177 EFFECT OF 3-HYDROXY-3-METHYLGLUTARYL-COA REDUCTASE INHIBITORS ON FASTING BLOOD SUGAR. Issue 1 (1st January 2007) - Sukhija, R.; Bursac, Z.; Sachdeva, R.; Sinha, A.; Mehta, J. L.
Abstract : Background: 3-Hydroxy-3-methylglutaryl-CoA reductase inhibitors (statins) reduce serum cholesterol and cardiovascular morbidity and mortality. But the effect of statins on glucose metabolism is unclear. Some studies have suggested that statins may cause hyperglycemia by increasing calcium concentration in the islet cells, leading to a decrease in insulin release, or by decreasing GLUT 4-mediated peripheral glucose uptake. Methods: We analyzed data in 345, 417 patients (mean age 61 ± 15 years, 94% males, 6% diabetics, 20% statin users) from the Veterans Affairs VISN 16 database. We studied change in fasting blood sugar (FBS) in this population over a mean time of 2 years between the first available measurement and the last measurement from the most recent recorded visit. Data were limited to patients who had two FBS measurements. In the diabetic group, a diagnosis of diabetes had to be present before the first FPG measurement. Results: Among nondiabetics, FBS increased with statin use from 97.8 to 105.2 mg/dL, and among nonstatin users, FPG increased from 96.6 to 101.6 mg/dL over the period of observation (increase in FBS with statin use; p < .0001). Among diabetics, FBS increased with statin use from 101.7 to 140.8 mg/dL, and among nonstatin users, FBS increased from 100.4 to 129.9 mg/dL (increase in FBS with statin use; p < .0001). After adjustment for age, use of aspirin, beta-blockers, and angiotensin-converting enzyme inhibitors, the change in FBS in nondiabetic statin users was +6.4 mg/dL (vs +5.2 mg/dL in nonstatin users, p < .0001), and for diabetic statin users, it was +38.9 mg/dL (vs +29.8 in nonstatin users, p < .0001). Conclusion: Statin use increases FBS in diabetic as well as nondiabetic patients. This relationship between statin use and rise in FBS is independent of age and use of aspirin, beta-blockers, and angiotensin-converting enzyme inhibitors.